APLIKASI KULINER SEBLAK TING-TING BERBASIS WEBSITE (Studi Kasus : Kedai Seblak Ting-Ting) - Lisana, Dede Nuri Haifa; Wahyuni, Tantri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Culinary MSMEs face challenges in leveraging digital technology to expand their market and improve their services. Seblak Ting-Ting Shop in Majalengka still relies on social media for promotions and ordering, resulting in less than optimal transaction management. This research aims to design a website-based culinary application that simplifies ordering, improves operational efficiency, and expands market reach. The development method used is the Waterfall method, encompassing requirements analysis through observation and interviews, design using UML (use case, activity, sequence, and class diagrams), implementation using PHP, CSS, and JavaScript, and testing using black box testing. The results show that the application can be accessed via PC or mobile devices, with key features including menu information, online ordering, a shopping cart, stock management, and order confirmation. Testing demonstrated that all functions functioned as expected. This system facilitates customer access to information and transactions, while also helping the shop owner manage sales data in a more structured manner. Thus, the developed application can improve service, operational efficiency, and expand the market reach of Seblak Ting-Ting Shop.